2003
DOI: 10.1242/jcs.00684
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of actin filaments by myosin II is a major contributor to cortical integrity and cell motility in restrictive environments

Abstract: Cells are frequently required to move in a local environment that physically restricts locomotion, such as during extravasation or metastatic invasion. In order to model these events, we have developed an assay in which vegetative Dictyostelium amoebae undergo chemotaxis under a layer of agarose toward a source of folic acid [Laevsky, G. and Knecht, D. A. (2001). Biotechniques 31, 1140-1149]. As the concentration of agarose is increased from 0.5% to 3% the cells are increasingly inhibited in their ability to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 50 publications
2
97
0
Order By: Relevance
“…This result suggests that an important contribution to the traction forces is made by actin polymerization (2) with possible contributions from myosin I (29). The importance of MyoII for motility on a flat surface may stem from its function in cytoskeletal organization and cortical integrity (9), rather than from the traction forces produced by its motor activity. A notable fraction of the myoII Ϫ cells in our experiments never become organized, remaining round and static.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that an important contribution to the traction forces is made by actin polymerization (2) with possible contributions from myosin I (29). The importance of MyoII for motility on a flat surface may stem from its function in cytoskeletal organization and cortical integrity (9), rather than from the traction forces produced by its motor activity. A notable fraction of the myoII Ϫ cells in our experiments never become organized, remaining round and static.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MyoII contractility facilitates rear retraction. Supporting this idea are the inability of myoII Ϫ cells to move on highly adhesive substrates (7), and their failure to move in the constrained space under a layer of agarose or in a 3D aggregate of cells (8,9). Despite significant progress in the understanding of the biochemistry of the cytoskeleton, the analysis of the spatiotemporal events that enable cell movement is in its infancy.…”
mentioning
confidence: 99%
“…Although unbound integrins are freely diffusive in the membrane plane, ligand binding promotes rapid attachment of integrins to actin filaments (Felsenfeld et al, 1996). Myosin II is an effective F-actin cross-linker (Laevsky and Knecht, 2003), and myosin-driven bundling and alignment of actin filaments carrying ligand-bound integrin complexes could then lead to the clustering of integrin-cytoskeleton complexes (Chrzanowska-Wodnicka and Burridge, 1996). Alternatively, myosin-dependent forces acting on integrin complexes could induce conformational changes in associated mechanosensitive proteins.…”
Section: Discussionmentioning
confidence: 99%
“…5B). Laevsky and Knecht (20) have also reported that myosin II-null cells drag a long tail containing GFP-ABD, which is especially prominent under an agarose sheet but also present in liquid media. In certain mammalian cell lines, depletion of myosin II results in the formation of similar F-actin-containing long tails (37).…”
Section: F) Migrating Talin A-null Cell Observed By Interference Reflmentioning
confidence: 95%
“…By analogy to the cytokinesis of myosin II-null cells, in which the division process is driven by opposite movement of the daughter cells (2), the above results suggest that the active polar elongation by the pseudopodia at both polar regions substantially contributes to the separation of the daughter cells in talin Anull cells. When the polar elongation was inhibited by pressing the cells under a sheet of 3% (wt/vol) agarose (20), wild-type cells still completed furrow ingression (Fig. 3B, Upper), but talin A-null cells failed to constrict the furrow.…”
Section: Talin a Is Required For Normal Tail Retraction In Directed Cellmentioning
confidence: 99%